The Effect of PjBL-STEM Integrated with Green Chemistry Principles on Enhancing Creative Thinking Skills and Environmental Literacy - Wahyudi, Haekal; Gani, Abdul; Syukri, Muhammad; Fazli, Rahmad Rizki; Safrijal, Safrijal (EduChemia: Jurnal Kimia dan Pendidikan, 2025)
The demands of 21st-century competition require several fundamental competencies, one of which is creativity. Additionally, the affective domain, particularly environmental awareness, has received increasing international attention. This study aims to examine the effect of implementing PjBL-STEM integrated with green chemistry principles in enhancing students' creative thinking skills and environmental literacy. The research employed a quasi-experimental design with a nonequivalent control group approach involving 10th-grade students at SMAN 1 Baitussalam. Class X IPAS 1 served as the experimental group, whereas Class X IPAS 2 served as the control group. The research instruments included validated learning material evaluation sheets, creative thinking skills test items, and environmental literacy comprehension tests, all of which were reviewed by experts and analyzed empirically. The data analysis techniques involved N-Gain tests and independent sample t tests with a significance level of 0.05. The hypothesis testing results revealed significant N-Gain scores for both creative thinking skills and environmental literacy (p < 0.001). These findings indicate a significant difference in the improvement of creative thinking skills and environmental literacy understanding between the experimental and control groups following the implementation of the PjBL-STEM model integrated with green chemistry principles.